Benchmarking minibus safety in Abu Dhabi, United Arab Emirates - David Logan (588171) (2015)
The Department of Transport (DoT) in Abu Dhabi has recognised that while minibuses play a key role in transporting people within the United Arab Emirates, levels of fatal and serious injury among minibus occupants in crashes are high. As a first step toward addressing this problem, the DoT commissioned a benchmarking study to gain an understanding of the state of the minibus fleet, focusing on fundamental vehicle safety aspects, as well as fitment rates of safety features such as airbags and stability control systems. Furthermore, the in-service condition of vehicles was also assessed. Data was collected from 566 minibuses in Abu Dhabi and Dubai, comprising more than 80 separate data points characterising the presence, nature and condition of each vehicle. An innovative system was developed to combine these variables to yield a weighted safety score that allowed them to be grouped into categories for later input into a benefit cost analysis of a replacement program. A star rating system was used for the categorisation process because it allows for good discrimination between safety levels while remaining easy to comprehend. The results of the benchmarking study showed that despite the fleet being quite uniform by make and model, there was considerable variation among individual vehicles in terms of seat belt fitment rates and rear passenger compartment seat mounting integrity in particular. Many vehicles in current operation are deficient both in terms of primary and secondary safety, compounded by inconsistent fitment of passenger seat belts. This in-depth survey has provided significant additional information unavailable from registration data and provides a valuable insight into the state of minibus safety in the UAE. The data acquired will be used to conduct a benefit cost analysis targeted at determining the optimal means for implementing significant improvements to the minibus fleet. Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.25